2015
DOI: 10.1080/13102818.2015.1092885
|View full text |Cite
|
Sign up to set email alerts
|

Cone beam computed tomography evaluation of maxillary molar root canal morphology in a Turkish Cypriot population

Abstract: The aim of this retrospective study was to review, analyse and characterize the root canal morphology of maxillary molars, using cone beam computed tomography (CBCT), in a group of the Turkish Cypriot population. The sample for this cross-sectional study consisted of retrospective evaluation of CBCT scans of 290 adult patients (age range 16À80). The number of roots and their morphology, the number of canals per tooth and the root canal configurations were also classified according to the method of Vertucci. Pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 31 publications
3
16
0
1
Order By: Relevance
“…Table 3 shows the number of roots and root canals of maxillary third molar among different populations [41,42,[45][46][47][48][49][50][51]. The most common root canal configuration for maxillary third molar is type I (1-1) followed by type II (2-1) (Table 4) [42,47,50,51]. The incidence of C-shaped canals in this tooth was reported in two studies: in the USA (2.2%) [45] and in China (8.5%) [51].…”
Section: Maxillary Third Molarmentioning
confidence: 99%
“…Table 3 shows the number of roots and root canals of maxillary third molar among different populations [41,42,[45][46][47][48][49][50][51]. The most common root canal configuration for maxillary third molar is type I (1-1) followed by type II (2-1) (Table 4) [42,47,50,51]. The incidence of C-shaped canals in this tooth was reported in two studies: in the USA (2.2%) [45] and in China (8.5%) [51].…”
Section: Maxillary Third Molarmentioning
confidence: 99%
“…Furthermore, studies using the clearing technique or sectioning using a dental operating microscope have shown higher detection rates than radiographic and CBCT examinations. 22 In the present study, canal configurations were identified according to Vertucci's classification system (Graph 2), revealing the most prevalent type as Type II in 83.5%. According to Rwenyonyi et al, type I was the most frequent, accounting up to 75.1 to 100%.…”
Section: Discussionmentioning
confidence: 69%
“…In Italy, the frequency of upper second molars with four roots was described with 1.27% ( n = 157) [11]. Comparable results were demonstrated in Greece (1.24%, n = 402) [12], in Cyprus (1.37%, n = 438) [13], and in the Portuguese study mentioned above (1.44%, n = 277) [3]. On the other hand, in East Asia, lower occurrence rates of this rare morphological anomaly were identified in population-based CBCT studies in Thailand (0.22%, n = 457) [9], South Korea (0.49%, n = 820) [14], and China (0.28%, n = 1066 [15]; 0.77%, n = 519 [16]; 0.98%, n = 1226 [17]; and 1.12%, n = 979 [18]).…”
Section: Discussionmentioning
confidence: 99%